Chronic alcohol intake abolishes the relationship between dopamine synthesis capacity and learning signals in the ventral striatum. (26th December 2014) - Deserno, Lorenz; Beck, Anne; Huys, Quentin J. M.; Lorenz, Robert C.; Buchert, Ralph; Buchholz, Hans‐Georg; Plotkin, Michail; Kumakara, Yoshitaka; Cumming, Paul; Heinze, Hans‐Jochen; Grace, Anthony A.; Rapp, Michael A.; et al.
Abstract Drugs of abuse elicit dopamine release in the ventral striatum, possibly biasing dopamine‐driven reinforcement learning towards drug‐related reward at the expense of non‐drug‐related reward. Indeed, in alcohol‐dependent patients, reactivity in dopaminergic target areas is shifted from non‐drug‐related stimuli towards drug‐related stimuli. Such 'hijacked' dopamine signals may impair flexible learning from non‐drug‐related rewards, and thus promote craving for the drug of abuse. Here, we used functional magnetic resonance imaging to measure ventral striatal activation by reward prediction errors (RPEs) during a probabilistic reversal learning task in recently detoxified alcohol‐dependent patients and healthy controls (N = 27). All participants also underwent 6‐[18F]fluoro‐DOPA positron emission tomography to assess ventral striatal dopamine synthesis capacity. Neither ventral striatal activation by RPEs nor striatal dopamine synthesis capacity differed between groups. However, ventral striatal coding of RPEs correlated inversely with craving in patients. Furthermore, we found a negative correlation between ventral striatal coding of RPEs and dopamine synthesis capacity in healthy controls, but not in alcohol‐dependent patients. Moderator analyses showed that the magnitude of the association between dopamine synthesis capacity and RPE coding depended on the amount of chronic, habitual alcohol intake. Despite the relatively small sample size, a power analysis supports the reported results. Using a multimodal imaging approach, this study suggests that dopaminergic modulation of neural learning signals is disrupted in alcohol dependence in proportion to long‐term alcohol intake of patients. Alcohol intake may perpetuate itself by interfering with dopaminergic modulation of neural learning signals in the ventral striatum, thus increasing craving for habitual drug intake.